The privatization projects implemented by Ministry of Defence - Ibrahim, Abdul Rahman (2007)
Privatization project involves a reduction in the role of government depending on which functions are being assigned. Ministry of Defence (MINDEF) Malaysia started to implement the privatization policy in 1993 by means of using available assets for the purpose of project development. However, after 14 years of implementing this method, majority of the projects were abandoned and delayed. The aim of this study is to investigate the effectiveness of privatization project implemented by MINDEF through the identification of effective criteria and the strategy to improve the situation. The method of this study involved literature review, interview, data collection and the analysis is using an Average Index method. The process of data collection involved obtaining primary data from the respondents by conducting questionnaire survey from the selected personnel involved directly or indirectly in planning and managing the project. From the analysis of this study five most important criteria that influence the effectiveness of privatization project were identified including the agreement contents which protect the government interests; meets the client requirements; the ability to complete project in time; good implementation strategies and procedures; and developer with good organization. In conclusion, some criteria identified to improve the effectiveness of privatization project includes resolving land matters before project implementation; and the ability of developer to identify the client requirements